The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpls.2021.587482
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promising RILs for High Grain Zinc Through Genotype × Environment Analysis and Stable Grain Zinc QTL Using SSRs and SNPs in Rice (Oryza sativa L.)

Abstract: Polished rice is one of the commonly consumed staple foods across the world. However, it contains limited nutrients especially iron (Fe) and zinc (Zn). To identify promising recombinant inbred lines (RILs) for grain Zn and single plant yield, 190 RILs developed from PR116 and Ranbir Basmati were evaluated in two environments (E1 and E2). A subset of 44 contrasting RILs for grain Zn was screened in another two environments (E3 and E4). Phenotypic data was collected for 10 traits, viz., days to 50% flowering, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 112 publications
2
18
0
Order By: Relevance
“…Rice has been widely consumed as an essential food for human beings and grown around the world. Over half of the world's population constantly include rice in their diet (Rao et al, 2016;Nili et al, 2017;Sharifi et al, 2017;Poli et al, 2018;Suman et al, 2021) and Asian countries produce nearly 80% of rice in the world. Among rice growing countries in the world, India has the largest area under rice crop of about 44.1 million hectares with a production of 165.3 million tons; however, its productivity per unit area is low i.e 3.78 t ha -1 (Kesh et al, 2021).…”
mentioning
confidence: 99%
“…Rice has been widely consumed as an essential food for human beings and grown around the world. Over half of the world's population constantly include rice in their diet (Rao et al, 2016;Nili et al, 2017;Sharifi et al, 2017;Poli et al, 2018;Suman et al, 2021) and Asian countries produce nearly 80% of rice in the world. Among rice growing countries in the world, India has the largest area under rice crop of about 44.1 million hectares with a production of 165.3 million tons; however, its productivity per unit area is low i.e 3.78 t ha -1 (Kesh et al, 2021).…”
mentioning
confidence: 99%
“…Znrelated chromosome regions found in elite wheat cultivars can be utilized to inform gene transfer studies from Znaccumulating wild species, as carried out between the high-Zn and -Fe Aegilops species and bread wheat (Sharma et al, 2018). Improved rice genome sequences allowed the exploitation of markers, such as simple sequence repeats and single-nucleotide polymorphisms, to identify QTLs for grain Zn and yield in recombinant inbred lines, which led to the establishment of stable lines with desired traits (Suman et al, 2021). As such, QTL analysis of rice doubled haploid lines identified candidate genes associated with both agronomic traits, yield and high concentrations of Zn in grains, for example, genes encoding transporters such as OsZIP6, but also transcription factors (e.g., OsGATA8) and GTPases involved in endosperm protein deposition (e.g., OsSar1) (Calayugan et al, 2020).…”
Section: Genetic Biofortification Approaches For Znmentioning
confidence: 99%
“…More recently, Liu et al (2021a) reported that a grain zinc content ranging from 38.22 to 101.38 µg/g in a Chinese wheat mini core collection contained 246 germplasms. However, there have been few large‐scale analyses of endosperm iron and zinc contents in rice and wheat (Zhang et al, 2018a; Suman et al, 2021). In a set of 698 rice germplasms, the concentrations of iron and zinc in the polished rice ranged from 0.9 to 9.1 µg/g and 5.8 to 29.6 µg/g, respectively (Zhang et al, 2018a).…”
Section: Progress In the Biofortification Of Rice And Wheat With Iron...mentioning
confidence: 99%
“…An association analysis of zinc content of 40 genotypes in three environments showed that single nucleotide polymorphisms located in three putative candidate genes on chromosomes 3 and 7 are associated with high zinc content in polished rice (Babu et al, 2020). An analysis of zinc contents in brown and polished rice from 190 recombinant inbred lines (RILs) in four environments identified two major QTL ( qZPR.1.1 and qZPR.11.1 ) for grain zinc content in polished rice on chromosomes 1 and 11, and a common major QTL ( qZBR.2.1 and qZPR.2.1 ) for zinc content in brown and polished rice was identified on chromosome 2 (Suman et al, 2021).…”
Section: Progress In the Biofortification Of Rice And Wheat With Iron...mentioning
confidence: 99%